La pratique du ṣulḥ dans les oasis du Grand Touat : justice consensuelle et juridiction islamique dans une société saharienne du xviiie siècle - Ismail Warscheid (Revue des Mondes Musulmans et de la Méditerranée)
During the early modern period (fifteenth-eighteenth centuries), the oasis of Tuwāt in present-day southern Algeria became one of the most important centers of Islamic learning in the Sahara. The spread of scholarship across the oasis accompanied the formation of powerful Islamic legal institutions operating at a regional level. This article analyzes the work of these institutions by focusing on the practice of compromise settlements (ṣulḥ). Empirically, our research is based on the close examination of a series of comprehensive collections of casuistic jurisprudence (nawāzil) compiled by local scholars between 1750 and 1850. The extraordinary richness of the materials conserved in these collections allows us, on the one hand, to show how the ṣulḥ was integrated into judicial decision-making processes as a device to complement and support legal rulings (ḥukm). On the other hand, we seek to illustrate how litigation was embedded in social relations marked by tribal structures and decentralized political power.